KUALITAS PELAYANAN DAN PROMOSI MEMPENGARUHI KEPUTUSAN MAHASISWA KULIAH DI STIE BENTARA PERSADA BATAM - Tamba, Imelda; Dabur, Feliks; Ester, Ester (Ensiklopedia Sosial Review, 2020)
The study of the research that the researchers did was the influence of Service Quality and Promotion on Student Decisions. Lecture at STIE Bentara Persada Batam. With the object of reseach on STIE Bentara Persada Batam students. The purpose of this study was to determine the effect of Service Quality and Promotion on Student Decision Lecture at STIE Bentara Persada Batam. This study used a sample of 70 students at STIE Bentara Persada Batam with the chosen sample technique being saturated sampling. Data collection techniques in this study used a questionnaire. The results showed that, Service Quality and Promotion partially had a positive and significant effect on Student Decision Lecture at STIE Bentara Persada Batam. The regression analysis results obtained a coefficient of determination (R2) of 0.175which means that student decisions areinfluenced by Service Quality and Promotion by 17.5%, while the remaining 82.5% is influenced by other variables not examined inthis study.